Pre-Truth Life in Post-Truth Times - Joel Backström (Nordic Wittgenstein Review, 2019)
Clearing philosophical ground for diagnoses of the contemporary ‘post-truth’-problematic, this article discusses the systematic and ineliminable ambivalence of claims to truth in public discourse and collective life generally, where truth cannot ultimately be disentangled from untruth. Truth becomes a problem in the relevant sense only where matters are morally-existentially charged, so that acknowledging truth threatens, e.g., loss of self-respect, and self-deception becomes tempting, individually and collectively. To the extent that our life is marked by injustice and destructiveness, it is necessarily also marked by systematic falsification, a conspiracy to deny the truth about it, about us. Collective life exhibits pervasive hostility to interpersonal (moral) understanding, which is repressed through collectively established fake ‘understandings’ and regimes of respectability. The fact/opinion and fact/value distinctions function as defences against understanding, while meaning and truth are seen as things to be determined rather than understood, and the concept of representatability, how things can be made to appear, becomes central. However, standard philosophical views on truth, meaning and morality render the problematic sketched here invisible, because they effectively move – as Wittgenstein arguably realised – wholly within the collective perspective that needs to be problematised.